Multihop relaying for broadband wireless access systems at 800 and 3500 MHz in rural areas. Issue 2 (5th February 2014) - Chee, Kin Lien; Feng, Wei; Kürner, Thomas
Abstract This paper addresses the coverage enhancement for broadband wireless access (BWA) at 800 and 3500 MHz in a rural scenario in north Germany using multi‐hop relay concepts. The investigation is divided into two phases: In phase I, the coverage of a single BWA system in a rural area is predicted and verified with measurement data. In phase II, the coverage from the BWA system is analyzed and enhanced through the deployment of relay stations. The number of relay stations required for each carrier frequency is determined, and the positions of the relay stations are identified via three different relay placement algorithms, namely path‐loss‐based, distance‐based, and hybrid algorithms. At 800 MHz, the path‐loss‐based algorithm requires seven relay stations to achieve an overall coverage of 95%. The hybrid and distance‐based algorithms require 11 and 14 relay stations, respectively, to achieve the same coverage. At 3500 MHz, path‐loss based and hybrid algorithms require 19 and 16 relay stations, respectively, to achieve the same coverage. The distance‐based requires 20 relay stations to achieve an overall coverage of 82%. Further increase of relay stations has led to higher interference. Lastly, the transmit power of the relay station is optimized via an intelligent power allocation scheme. The results show that 20% of the total transmit powers from 14 relay stations can be saved at 800 MHz whereas 18% of the total transmit powers from the 20 relay stations can be saved at 3500 MHz.